Blunted hyperphagic and c-Fos immunoreactivity responsiveness to an orexigen, butorphanol tartrate, in aged rats. (15th October 2019) - Olszewski, Pawel K.; McColl, Laura K.; Herisson, Florence M.; Klockars, Anica; Levine, Allen S.
Highlights: Aged rats given standard chow show diminished orexigenic response to butorphanol tartrate (BT). Higher doses of BT are necessary to increase palatability-driven intake of calorie-dilute fluids and energy-dense chow. Brainstem and hypothalamic c-Fos profiles are similar in BT-injected adult and aged rats. c-Fos expression is blunted in the central and basolateral amygdala in aged rats compared to adult individuals. Abstract: Administration of the mixed opioid agonist-antagonist butorphanol tartrate (BT) has been shown to robustly increase food intake in rodent models utilizing adult and young animals. BT at orexigenic doses increases c-Fos-immunoreactivity (IR) in brain areas associated with feeding for energy as well as for reward, including the paraventricular nucleus of the hypothalamus, central nucleus of the amygdala and nucleus of the solitary tract. Interestingly, aged rats given standard chow show a diminished feeding response to BT. It is not known, however, whether this weakened orexigenic response in aged animals extends to palatable tastants and whether it is accompanied by changes in brain activation. In the current study, we injected adult (11–12 months) and aged (26–27 months) rats with BT and studied the effect on intake of chow and palatable ingestants (liquid and solid). We found that BT produced only a moderate increase in consumption of bland or palatable chow as well as sweet solutions (both caloric and non-caloric) in aged rats, and that higher BT doses are required to generate such eating in old animals compared to adults. This blunted hyperphagia after BT is accompanied by diminished c-Fos IR in the central and basolateral amygdala, regions that process emotional aspects of behaviors, including food intake. Thus, aged rats exhibit diminished responsiveness to the feeding effects of BT, independent of the type of diet; and it appears to be due, in part, to diminished neural activity in central circuits involved in emotional behavior.